Alcohol Use, Depressive Symptoms, and Impulsivity as Risk Factors for Suicide Proneness among College Students - Dvorak, Robert D. (2013)
BACKGROUND: Alcohol use, depression, and suicide are significant public health problems, particularly among college students. Impulsivity is associated with all of these factors. Additionally, impulsivity increases the effects of negative mood and alcohol use on maladaptive behavior. METHODS: The current cross-sectional study examined the association between the four-factor model of impulsivity (urgency, (lack of) perseverance, (lack of) premeditation, and sensation seeking), depressive symptoms, and alcohol use as predictors of suicide proneness among college students. Participants (n =1100) completed online assessments of demographics, impulsivity, depressive symptoms, and suicide proneness. RESULTS: All predictors were positively related to suicide proneness. The relation between depressive symptoms and suicide proneness was moderated by (lack of) perseverance, alcohol use, and joint interactions of urgency × alcohol use and sensation seeking × alcohol use. Despite some paradoxical findings regarding the depressive symptoms-suicide proneness relation when only one risk factor was elevated, the average level of suicide proneness increased as risk factors increased. LIMITATIONS: This cross-sectional self-report data comes from a non-clinical sample of college students from a homogeneous background, limiting generalizability and causal predictions. CONCLUSIONS: Overall, these findings indicate that the association between depressive symptoms and suicide proneness varies considerably by different facets of impulsivity and alcohol use. The results suggest that clinical risk-assessments should weigh two forms of impulsivity (urgency and sensation seeking) as particularly vital in the presence of heavy alcohol use. These findings highlight the importance of considering and exploring moderators of the mood-suicide relationship.